2005
DOI: 10.1038/sj.leu.2403987
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of human multiple myelomas and myeloid leukemias to the proteasome inhibitor I

Abstract: The proteasome inhibitor PSI is potently cytotoxic in vitro against human chronic myeloid leukemia (CML) and acute myeloid leukemias (AML). Here, we have tested proteasome inhibitor I (PSI) in a panel of 11 human multiple myeloma (MM) cell lines and found that it has antiproliferative activity, with an IC 50 between 4.5 and 557 nM at 48 h. PSI potentiated the toxicity of a number of chemotherapeutic agents in myeloid leukemia but not in MM cell lines, while in combination with therapeutic proteasome inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…These studies used BCR-ABL ϩ cell lines both sensitive and resistant to IM and demonstrated antiproliferative and apoptotic effects. [39][40][41] In addition, the PI Z-Ile-Glu(OtBu)-Ala-Leucinal selectively inhibits colony formation by CD34 ϩ BCR-ABL ϩ progenitor cells. 41 Despite promising in vitro effects, there are little in vivo data.…”
Section: Introductionmentioning
confidence: 99%
“…These studies used BCR-ABL ϩ cell lines both sensitive and resistant to IM and demonstrated antiproliferative and apoptotic effects. [39][40][41] In addition, the PI Z-Ile-Glu(OtBu)-Ala-Leucinal selectively inhibits colony formation by CD34 ϩ BCR-ABL ϩ progenitor cells. 41 Despite promising in vitro effects, there are little in vivo data.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of down-regulation of HLA class I on CD34 ϩ and healthy cells is consistent with reports that MM is significantly more sensitive to proteasome inhibition compared with CD34 ϩ bone marrow progenitor cells. 42,43 A single dose of bortezomib also down-regulated HLA class I on CD138-purified MM cells in vivo. We confirmed that HLA-C was equally down-regulated because HLA-C is the principal inhibitory ligand for KIR on NK cells.…”
mentioning
confidence: 99%
“…Bortezomib has been approved for treatment of multiple myeloma progressing on prior therapy. 4,9 Selective induction of cell death mediated by proteasome inhibition has been well documented in various malignancies, among them multiple myeloma, ovarian cancers, leukemias, and T and B cell lymphomas. 4,10 However, the effects of proteasome inhibition on non-malignant developing and mature lymphocytes remain largely unknown.…”
mentioning
confidence: 99%